MAGNETIC HYPERTHERMIA AS A CANCER TREATMENT IN BRAZIL: TWO DECADES OF SCIENTIFIC ADVANCES - Borges, Roger; Pelosine, Agatha Maria; Oliveira, Juliana Soares da Silva de; Jesus, Luccas Correa Teruel de de; Marchi, Juliana (Revista da Associação Brasileira de Pesquisadores/as Negros/as (ABPN), 2022)
In Brazil, studies in magnetic hyperthermia, i.e. a treatment of cancer based on heating cancer cells, started in the late 90s, mainly centered in the Southeast and Central West of Brazil, where consolidated institutions are found, i.e., institutions that have done research in the field since the 90s and 2000s. However, rising institutions, i.e., institutions that have recently contributed to the field, are found in all Brazil’s regions. Usually, consolidated and rising institutions collaborate between them and with international institutions overseas, leading to a significant role of Brazil in the international scenario, mainly in Latin America. Furthermore, researchers in Brazil have contributed with theoretical and experimental studies from which most are interdisciplinary. Finally, despite advances in magnetic hyperthermia in Brazil, there is a lack of clinical trials to make this treatment available in clinical practice.